Branded Content Analysis of Kahf Web Series 'Demi Masa' - Ersal Bioldy; Hasan Ali Murtadha; Yulinda S. Permatasari (Jobmark: Journal of Branding and Marketing Communication, 2024)
This study analyzes the content of the Kahf web series, a skincare and grooming brand for men in Indonesia, entitled 'Demi Masa,' Season 1, as a strategy for building brand awareness. Using the Branded Content Analysis (BCA) method with a qualitative-instrumental approach, the results show that the marketing strategy of Kahf products and the storyline in the series are very natural to the identity of the Kahf product itself. The narrative touches the audience through the image's appearance, the actors who play the role, and the placement of Kahf products that are adjusted to the storyline. It can be seen that the narrative of 'Demi Masa', which is inspired by one of the verses in the holy book of the Koran, plays a significant role in shaping the Islamic identity of the Kahf brand and in Kahf's efforts to preach and invite consumers to contemplate through the brand narrative about the importance of time. This study provides an in-depth understanding of the strategy of building brand awareness for a product through storytelling and creative content, as well as inspiring other brands.